X-ray sources in dwarf galaxies in the Virgo cluster and the nearby field. Issue 4 (15th June 2016) - Papadopoulou, Marina; Phillipps, S.; Young, A. J.
Abstract : The extent to which dwarf galaxies represent essentially scaled down versions of giant galaxies is an important question with regards the formation and evolution of the galaxy population as a whole. Here, we address the specific question of whether dwarf galaxies behave like smaller versions of giants in terms of their X-ray properties. We discuss two samples of around 100 objects each, dwarfs in the Virgo cluster and dwarfs in a large Northern hemisphere area. We find nine dwarfs in each sample with Chandra detections. For the Virgo sample, these are in dwarf elliptical (or dwarf lenticular) galaxies and we assume that these are (mostly) low-mass X-ray binaries (LMXB) [some may be nuclear sources]. We find a detection rate entirely consistent with scaling down from massive ellipticals, viz. about one bright (i.e. L X  > 10 38  erg s −1 ) LMXB per 5 × 10 9  M⊙ of stars. For the field sample, we find one (known) Seyfert nucleus, in a galaxy which appears to be the lowest mass dwarf with a confirmed X-ray emitting nucleus. The other detections are in star-forming dwarf irregular or blue compact dwarf galaxies and are presumably high-mass X-ray binaries (HMXB). This time, we find a very similar detection rate to that in large late-type galaxies if we scale down by star formation rate, roughly one HMXB for a rate of 0.3 M⊙ per year. Nevertheless, there does seem to be one clear difference, in that the dwarf late-type galaxies with X-ray sources appear strongly biased to very low metallicity systems.